Effect of Candida antarctica lipase B immobilization on the porous structure of the carrier - Miletic, Nemanja; Vuković, Zorica; Nastasović, Aleksandra; Loos, Katja (Macromolecular Bioscience, 2011)
A series of poly(GMA-co-EGDMA) resins with identical composition but varying particle sizes, pore radii, specific surface areas and specific volumes are studied to assess how Candida antarctica lipase B immobilization affects the porosity of the copolymer particles. Mercury porosimetry reveals a significant change in the average pore size (up to 6.1-fold), the specific surface area (up to 3.2-fold) and the specific volume (up to 2.1-fold) of the epoxy resin. A similar behaviour is observed for glutaraldehyde-modified epoxy resins. The influences of the resin porosity properties on the loading of Candida antarctica lipase B during immobilization and on the hydrolytic activity (hydrolysis of p-nitrophenyl acetate) of the immobilized lipase are studied. Published